Comparative Analysis of Soil Phosphorus Determination Methods and Their Correlation with Plant Phosphorus in Standing Wheat Crops - Zaryab Khan; Aftab Tabasum; Dost Muhammad; Maria Mussarat; Javaid Hassan (Turkish Journal of Agriculture: Food Science and Technology, 2024)
This study compared the accuracy of various soil phosphorus assessment methods to measure the soil's ability to supply plants with phosphorus over a brief period in the field. Twenty individual soil samples were collected from a standing wheat (Triticum aestivum L) crop at depths ranging from zero to twenty centimeters. An equivalent plant spike sample was also procured from the soil sampling fields. In comparison to the wet acid digestion method used to detect phosphorus in plants, several methods were utilized to assess phosphorus in the soil, including resin extractable phosphorus, AB-DTPA extractable phosphorus, NaHCO3 extractable phosphorus, water-soluble phosphorus in suspension, and paste. The levels of variation and deficiency of phosphorus, which were found by different methods followed different patterns as shown by the fact that, AB-DTPA method finds phosphorus deficiency in 20% of samples while on the other hand, Olsen method finds phosphorus deficiency in 80% of samples. Even with such a small sampling area, none of the procedures showed a significant correlation with any other method that might account for uneven variation among the samples when determined by distinct procedures. However, corrections were observed to a certain degree between ammonium bicarbonate-diethylenetriaminepentaacetic acid (AB-DTPA) extractable and resin, as well as between other procedures and the plant P scale. Both resin and ammonium bicarbonate-diethylenetriaminepentaacetic acid (AB-DTPA) had a strong relationship with plant phosphorus, with the former showing a significant correlation of 0.48 and 0.21, respectively. Hence Resin and AB-DTPA methods are recommended for the determination of phosphorus under certain soil and plant conditions.